ANALISIS PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TIMUR TAHUN 2015-2023 - Firda, Rochmania; Istiyani, Nanik; Yuliati, Lilis; Luthfi, Agus (Jurnal Ekuilibrium, 2025)
The existence of the Covid-19 pandemic has an impact on the decline in the economy and the decline in labor absorption is not fully absorbed, so the government must also provide jobs. If labor absorption is optimally absorbed, it will affect the increase in the economy so that there is community welfare. The purpose of this study is to analyze how the influence of UMK, PDRB and HDI on labor absorption in East Java Province in 2015-2023 with a research model of panel data regression analysis. In other words, panel data is data obtained from cross sections that are repeatedly observed on the same individual unit at different times. Then a description of the behavior of several objects will be obtained over several time periods and see how the influence of the independent variables is partially through the t test and simultaneously through the F test on the dependent variable. And, knowing how much percentage of the independent variables in this study affect the dependent variable. The estimation results show that UMK does not affect labor absorption in East Java Province, PDRB affects labor absorption in East Java Province and HDI does not affect labor absorption in East Java Province